The Profile of Questioning and Reinforcement Skills of Pre-Service Teachers in Biology Learning of the Tenth Grade - Uthary Relanda Regiska; Meilinda Meilinda; Anwar Yenny (Postgraduate, University of Mataram, 2022)
This study aims to find out how to apply the components of pre-service biology teachers’ questioning and reinforcement skills. This study was conducted at UPT SMA Negeri 8 Ogan Ilir. The design used in this study is descriptive research. The instruments used were observation sheets and documentation in the form of video recordings. The application of basic questioning skills was seen from 7 aspects while for the application of advanced questioning skills, it is seen from 5 aspects. As for the application of reinforcement skills, it was seen from 4 aspects. The results showed that there was a difference in the number of applying questioning and reinforcement skills during the learning process. In general, pre-service teachers have implemented all components of basic and advanced questioning skills. However, the components of basic questioning skills of giving turns and distributing questions and advanced questioning skills of increasing interaction among students still rarely appear. Meanwhile, the application of the reinforcement skill components of pre-service teachers has been applied in the learning process but still tends to be monotonous.